Plasmid parB contributes to uropathogenic Escherichia coli colonization in vivo by acting on biofilm formation and global gene regulation - Song, Ningning; De Greve, Henri; Wang, Quanjun; Hernalsteens, Jean-Pierre; Li, Zhaoli (Frontiers in Molecular Biosciences, 2022)
The endogenous plasmid pUTI89 harbored by the uropathogenic Escherichia coli (UPEC) strain UTI89 plays an important role in the acute stage of infection. The partitioning gene parB is important for stable inheritance of pUTI89. However, the function of partitioning genes located on the plasmid in pathogenesis of UPEC still needs to be further investigated. In the present study, we observed that disruption of the parB gene leads to a deficiency in biofilm formation in vitro. Moreover, in a mixed infection with the wild type strain and the parB mutant, in an ascending UTI mouse model, the mutant displayed a lower bacterial burden in the bladder and kidneys, not only at the acute infection stage but also extending to 72 hpi. However, in the single infection test, the reduced colonization ability of the parB mutant was only observed at 6 hpi in the bladder, but not in the kidneys. The colonization capacity in vivo of the parB-complemented strain was recovered. qRT-PCR assay suggested that ParB could be a global regulator, influencing the expression of genes located on both the endogenous plasmid and chromosome, while the gene parA or the operon parAB could not. Our study demonstrates that parB contributes to the virulence of UPEC by influencing biofilm formation and proposes that the parB gene of the endogenous plasmid could regulate gene expression globally.